Utility-value change and the role of emotional cost in video-based learning: a matter of student teachers’ interpretation of experience - Dehne, Mathias; Gröschner, Alexander (Frontiers in Psychology, 2023)
Motivational and emotional characteristics influence teachers’ reflections on video clips from their own teaching. However, utility values and the role of emotional cost have not been considered yet in video-based research in teacher education. In the present study, 102 student teachers were randomly assigned to an intervention group (IG) with video-based documentation of a lesson and systematic writing assignment or to a control group (CG) with protocol-based documentation of a lesson and writing assignment. Multigroup latent change score analysis indicated that IG participants, on average, showed a 0.52 SDs higher increase in utility values than the CG three months after the teaching practicum. Emotional cost was negatively related to baseline utility-value scores but predicted latent change scores positively after the writing assignment. The study adds to the current repertoire of video-based learning opportunities by providing a systematic writing assignment targeting student teachers’ interpretation of experiences to leverage motivation.